The Role of Teachers in Using Audio Visual Media to Improve Learning Outcomes of Grade VI Students of SD Inpres Tulo in Indonesian Language Subject - Azazia, Nur; Lagandesa, Yun Ratna; Aqil, Muhammad; Hariana, Kadek; Putriwanti, Putriwanti (Journal of Educational Sciences, 2025)
This research aims to explore the teacher’s role in utilizing audiovisual media to improve the learning outcomes of sixth-grade students at SD Inpres Tulo in Bahasa Indonesia lessons. A descriptive qualitative method was used, employing observation, interviews, and documentation to collect data. The results indicate that audiovisual media significantly enhance students’ cognitive abilities (understanding texts and story structures), affective aspects (learning motivation and positive attitudes), and psychomotor skills (short story writing). Teachers act as designers, facilitators, and evaluators by integrating videos, animations, and audio recordings into lessons, which create an engaging and interactive classroom atmosphere. The average percentage of students who understand narrative structures increased from 40% to 75%, while active participation in discussions rose from 30% to 65%. However, several challenges remain, such as limited facilities and teachers’ technical readiness. The study concludes that well-planned integration of audiovisual media, supported by quality materials and teacher training, can optimize learning outcomes in Bahasa Indonesia. These findings highlight the importance of innovative teaching strategies to meet students’ diverse needs in the modern learning environment. The study suggests continuous improvement in media quality and technical support to overcome existing obstacles and maximize the positive impact on students’ academic performance.